Estimating the Impact of Official and Parallel Exchange Rates on Inflation in Sierra Leone. - Mohamed Samba Barrie; Emerson Abraham Jackson; Joseph Pessima (ZBW - Leibniz Information Centre for Economics, 2023)
This study examines the duality of the exchange rate market in Sierra Leone, delving into the distinct impacts of the official and parallel exchange rates (between the Leone and the United States Dollar) on inflation. Employing the Autoregressive Distributed Lag (ARDL) approach and utilizing annual time series data from 1980 to 2020, the research reveals that the depreciation of the Leone significantly influences inflation. This effect is more pronounced in the case of the parallel exchange rate, where a 1% depreciation results in a 1.26 percentage point increase in inflation, gradually decreasing to 0.92 percentage point over two years. Conversely, the depreciation of the official rate leads to a 0.43 percentage point increase inflation and subsequently to 0.52 percentage point increase in inflation for every 1% depreciation of the official exchange rate in the second year. The findings confirm the significance of both official and parallel exchange rates in influencing inflation, highlighting a substantial difference in their effects on the economy. Nevertheless, the results indicate no statistically significant long-term relationship between inflation and both the official and parallel exchange rates in Sierra Leone. Exchange rate depreciation, particularly in the parallel market, is shown to have a pronounced impact on inflation, necessitating careful oversight and regulation of the parallel market to ensure price stability. The study also uncovers the presence of foreign exchange market fragmentation, posing challenges to effective monetary policy and exchange rate management. Policy implications drawn from the research underscore the importance of regulating the parallel market to enhance transparency and stability. Integrating fragmented foreign exchange markets is deemed crucial for minimizing exchange rate pass through to inflation. Acknowledging the data limitations, the research suggests enriching future investigations by incorporating recent data, global economic factors, and investor sentiments, all of which have the tendency to affect exchange rate movements.
Keywords: 330; Official Exchange Rate; Parallel Exchange Rate; Inflation; exchange-rate-market-duality; Sierra Leone